Depression and Social Support During Antepartum Hospitalization: A Needs Assessment [19B]. (May 2017) - Young, Danielle; Preyss, Melissa; Sipsma, Heather; Hair, Stephanie; Siddiqui, Maryam
Abstract : INTRODUCTION: Antenatal hospitalization occurs in nearly one million women every year. The overall prevalence of perinatal depression is near 20% and is undefined in this population. We aimed to define rates of depression and social support in a historically understudied, primarily low-income, African-American population. METHODS: Fifty women who were hospitalized for at least 48 hours during pregnancy for maternal or fetal indications were screened with the Edinburgh Postnatal Depression Scale (EPDS) and Personal Resource Questionnaire (PRQ). An EPDS score of 10 or higher was considered a positive screen. RESULTS: Twelve (24%) participants had an EPDS score of 10 or greater; three (6%) scores were higher than 20. Average PRQ score was 146.5 (±25.97). Approximately 30% of participants disagreed that they belonged to a group to which they felt important, and 16% neither agreed nor disagreed on this item. 30% reported that they could not count on relatives or friends for help, and 66% were indifferent (somewhat agreed, were neutral, or somewhat disagreed) that others have similar problems. Parents (81.63%) were overwhelmingly selected as support for an urgent needs crisis, followed by significant other/spouse/partner (67.35%) and other relative (59.18%). CONCLUSION: One in four women who were hospitalized during pregnancy struggled with depressive symptoms. Some women may have difficulty identifying adequate social support, although many reported adequate support networks. Despite the frequency of antenatal hospitalization, nearly two thirds of women were unsure if others had similar problems. More research is needed to identify ways to support pregnant patients and decrease isolation during hospitalization.